Impact of Antiretroviral Therapy on Opportunistic Infections of HIV-Infected Children in the TREAT Asia Pediatric HIV Observational Database - Prasitsuebsai, Wasana (2014)
BACKGROUND: There are limited data on opportunistic infections (OI) and factors associated with their occurrence after highly active antiretroviral therapy (HAART) in Asian children. The use of HAART in Asia started much later than in developed countries and therefore reported findings may not be fully applicable to the pediatric HIV epidemic in Asia. METHODS: Retrospective and prospectively collected data from the TREAT Asia Pediatric HIV Observational Database cohort study from March 1993 to March 2009 were analyzed. OIs were defined according to WHO clinical staging criteria, and incidence rates calculated. Factors associated with the incidence of severe OIs were analyzed using random effects Poisson regression modeling. RESULTS: Of 2280 children in the cohort, 1752 were ever reported to have received ART, of whom 1480 (84%) started on HAART. Before commencing any ART, OIs occurred at a rate of 89.5 per 100 person-years. The incidence rate was 28.8 infections per 100 person-years during mono- or dual-therapy, and 10.5 infections per 100 person-years during HAART. The most common OIs both before and after ART initiation were recurrent upper respiratory tract infections, persistent oral candidiasis, and pulmonary tuberculosis. The incidence rates of WHO clinical stage 3 or 4 OIs after HAART were highest among children <18 months of age and those with low weight-for-age z scores, CD4 cell percentage <15%, and WHO stage 3 at HAART initiation. CONCLUSIONS: Despite dramatic declines in their incidence, OIs remained important causes of morbidity after HAART initiation in this regional cohort of HIV-infected children in Asia.